The effect of empty fruit bunches (EFB) mulching on oil palm plantation performances / Amru Al-As Mohd Asri - Mohd Asri, Amru Al-As (Faculty of Plantation and Agrotechnology, 2016)
Oil palm is the most important product from Malaysia that has helped to change the scenario of it's agriculture and economy. The fundamental principles of waste management are to minimize and recycle the waste, recover the energy and finally dispose the waste. In total, about 90 million mt of renewable biomass (trunks, fronds, shells, palm press fiber and the empty fruit bunches) are produced each year. The empty fruit bunches (EFB) represent about 9% of this total. EFB is a suitable raw material for recycling because it is produced in large quantities in localized areas. As the industries keep growing, the disposal of the biomass waste still does not have much option of right solution. It has become common situation faced by the oil palm plantation management sector. Mostly the management of the oil palm plantation will only depend on a few solution. There is not many oil palm plantation that practices the use of EFB as mulching. This study were carried to identify the effect of practising EFB as mulching to the oil palm yield. Also to identified the effect of mulching on the amount of fertilizer used before and after applying the EFB. The study were conducted in Ketengah Perwira Holding's Plantation located at Cukai, Kemamam. To identify the effect of applying the EFB, data of the oil palm yield in the plantation are taken and compared to each other. The data yield on the oil palm trees at age 10 year are recorded. To identify the effect, the oil palm yield data before and after replanting will be compared to see the difference. The reason data of the oil palm yield before and after were taken is because to show that the oil palm plantation have taken the data of yield before and after applying the mulching. The same method were used to identify the amount of fertilizer effected before and after apply the EFB. This case study had identified the effect of using EFB as mulching between the two time period which represent before and after.